1999
DOI: 10.2134/agronj1999.00021962009100030015x
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, Botanical Composition, and Nutritive Value of Swards Including Forage Chicory

Abstract: Pure stands of 'Grasslands Puna' chicory (Cichorium intybus L.) are productive and responsive to N fertilization in the eastern USA.We conducted a field experiment for 3 yr to investigate productivity and nutritive value of swards including chicory, orchard grass (Dactylis g/omerata L.), and birdsfoot trefoil (Lotus comicu/atus L.) as a func· tion of clipping frequency (3-and 6-wk intervals). Each treatment was replicated three times on an upland site of Dekalb series soil (loamy-skeletal, mixed, subactive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 11 publications
5
62
1
1
Order By: Relevance
“…In vitro organic matter disappearance was increased by the 12 IS treatment (Table 4). However, all values are indicative of high quality forage and surpass IVOMD concentrations reported for chicory growing under field conditions by Belesky et al. (1999).…”
Section: In Vitro Organic Matter Disappearance and Metabolizable Enermentioning
confidence: 54%
See 2 more Smart Citations
“…In vitro organic matter disappearance was increased by the 12 IS treatment (Table 4). However, all values are indicative of high quality forage and surpass IVOMD concentrations reported for chicory growing under field conditions by Belesky et al. (1999).…”
Section: In Vitro Organic Matter Disappearance and Metabolizable Enermentioning
confidence: 54%
“…(2000). Crude protein content across all IS treatments exceeded the requirement for sheep, beef and dairy cattle at all stages of production (National Research Council 1985, 1989, 1996) and also exceeded concentrations found in field‐grown chicory by Belesky et al. (1999).…”
Section: Crude Proteinmentioning
confidence: 84%
See 1 more Smart Citation
“…Chicory ( Cichorium intybus L.) can supplement mid‐ and late‐season forage production in eastern North America (Jung et al. 1996, Belesky et al. 1999, Kunelius and MacRae 1999) and most likely other regions with similar growing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Four thousand years ago, chicory roots were used as a substitute for coffee in ancient Egypt [18], [19]. Chicory has a higher content of sodium, zinc, copper, iron, calcium, magnesium and sulphur compared to ryegrass and lucerne [20], [21]. Thus, chicory supplementation in a grass mixture can supply protein, minerals and vitamins to livestock [22].…”
Section: Introductionmentioning
confidence: 99%